Digital Dopamine Economy : Kerangka Konseptual Neuroperilaku untuk Memahami Perilaku Finansial di Era Fintech - Tomy Octavian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
The rise of digital technology has reshaped the landscape of financial behavior, particularly through the integration of features such as e-wallets, cashback incentives, and gamification within financial applications. These developments indicate that financial decision-making is no longer driven solely by rational processes, as assumed in the Homo Economicus model, but is increasingly influenced by emotional and neurological mechanisms aligned with the Homo Psychologicus perspective. This study explores the relationship between the brain's dopaminergic system and digital stimuli that contribute to impulsive financial behavior in the fintech era, drawing from neuroeconomics, behavioral finance, and digital economics. Employing a narrative literature review method, the analysis synthesizes insights from multidisciplinary scholarly sources. The findings are organized into four central themes: the role of dopamine in reward processing and risk-taking, the impact of digital triggers such as notifications and flash sales, and moderating factors including personality traits, financial literacy, and Generation Z characteristics. The study proposes a conceptual framework of “Digital Dopamine Economy” to explain the interplay between external digital stimuli and internal neurobehavioral responses. Its primary contribution lies in advancing a theoretical model that bridges disciplines and offers a foundation for future empirical research and neuroscience-informed financial literacy initiatives.